2004
DOI: 10.1364/opex.12.002156
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh resolution Fourier domain optical coherence tomography

Abstract: We present, for the first time, in vivo ultrahigh resolution (~2.5 microm in tissue), high speed (10000 A-scans/second equivalent acquisition rate sustained over 160 A-scans) retinal imaging obtained with Fourier domain (FD) OCT employing a commercially available, compact (500x260mm), broad bandwidth (120 nm at full-width-at-half-maximum centered at 800 nm) Titanium:sapphire laser (Femtosource Integral OCT, Femtolasers Produktions GmbH). Resolution and sampling requirements, dispersion compensation as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
175
0
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 350 publications
(185 citation statements)
references
References 4 publications
1
175
0
6
Order By: Relevance
“…Broad-bandwidth superluminescent diode light sources, similar to the one used in this study, recently have been shown to enable UHR OCT image resolution performance approaching that of femtosecond lasers. [27][28][29][30][31][32][33][34][35][36][37][38] Our research prototype high-speed UHR OCT system has been described in detail in previous publications. [29][30][31][32][33] This system can acquire up to 25 000 axial scans per second, corresponding to ~49 images (512 axial scans per image) per second.…”
Section: Methodsmentioning
confidence: 99%
“…Broad-bandwidth superluminescent diode light sources, similar to the one used in this study, recently have been shown to enable UHR OCT image resolution performance approaching that of femtosecond lasers. [27][28][29][30][31][32][33][34][35][36][37][38] Our research prototype high-speed UHR OCT system has been described in detail in previous publications. [29][30][31][32][33] This system can acquire up to 25 000 axial scans per second, corresponding to ~49 images (512 axial scans per image) per second.…”
Section: Methodsmentioning
confidence: 99%
“…Depuis son invention au dĂ©but des annĂ©es 1990, l'OCT a connu de nombreux dĂ©veloppements. Dans l'OCT spectrale (ou OCT de Fourier), le balayage de la diffĂ©rence de marche est remplacĂ© par une mesure en parallĂšle du spectre du signal interfĂ©romĂ©trique, ce qui conduit Ă  une rĂ©duction spectaculaire du temps d'acquisition [4][5][6]. L'OCT en lumiĂšre polarisĂ©e, capable de rĂ©vĂ©ler les propriĂ©tĂ©s optiques de birĂ©fringence, apporte des informations supplĂ©mentaires sur la structure et la composition des tissus [7][8][9].…”
Section: L'oct Plein Champunclassified
“…Although a number of broadband light sources have been developed to improve axial resolution in time domain and SD-OCT [21][22][23][24], only a few broadband high-speed wavelength-swept light sources have been reported [25][26][27][28]. Semiconductor gain media can be easily incorporated into compact laser cavity designs and have been developed for many different spectral bands.…”
Section: Introductionmentioning
confidence: 99%